OPTIMIZATION OF THE FORMATION OF TECHNICAL-TACTICAL SKILLS IN YOUNG WRESTLERS (World Bulletin of Physical Education and Sports Science, 2025)
This article analyzes pedagogical innovative approaches aimed at optimizing the process of forming technical skills in young kurash wrestlers. Unlike traditional methods based on repetitive exercises, the scientific foundations of improving athletes' motor skills and decision-making speed through the use of game, situational, and problem-based learning technologies are presented. The research results show the advantage of the game method in improving the effectiveness of technical actions.
Keywords: Young wrestlers, technical and tactical skills, innovative, traditional, repeated exercises, motor skills and decision-making, effectiveness.